2017
DOI: 10.1021/acs.joc.7b02179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Ketosulfonamides Derived from Amino Acids and Their Conversion to β-Keto-α,α-difluorosulfonamides via Electrophilic Fluorination

Abstract: β-Ketosulfonamides derived from Boc or Cbz-protected amino acids bearing hydrophobic side chains were prepared in good to excellent yield by treating N-allyl, N-alkyl methanesulfonamides with n-BuLi, followed by reaction of the resulting carbanion with methyl esters of N-protected l-amino acids. The analogous reaction using the dianion derived from an N-alkyl methanesulfonamide proceeded in much lower yield. Electrophilic fluorination of the β-ketosulfonamides using Selectfluor in the presence of CsF in DMF at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, this reagent is very expensive; moreover, HCF 2 Cl, an ozone-depleting gas, is used for its preparation, and yields of the difluoromethanesulfonamides are usually very low. Therefore, we began our studies by developing an alternative approach to these compounds that does not require an ozone-depleting gas and can be prepared from readily available materials and reagents (Scheme ). Pyrrolidine sulfonamide 4a and sulfonamides 4b – 4d , which contain groups that are commonly used to protect the sulfonamide nitrogen (allyl, para- methoxybenzyl (PMB), 2,4-dimethoxybenzyl groups (DMB)), were subjected to n -BuLi and then N -methoxy- N -methyltrifluoroacetamide, which gave β-ketosulfonamides 5a – 5d in good to excellent yields. After some experimentation using the pyrrolidine derivative 5a as a model system, it was found that compound 6a could be obtained in 93% yield using 2.5 equiv of Selectfluor and Li 2 CO 3 in DMF for 3 h. Compound 6a could also be produced in a 78% yield using just 2.5 equiv of Selectfluor in DMF at 100 °C for 1 h (no base added).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this reagent is very expensive; moreover, HCF 2 Cl, an ozone-depleting gas, is used for its preparation, and yields of the difluoromethanesulfonamides are usually very low. Therefore, we began our studies by developing an alternative approach to these compounds that does not require an ozone-depleting gas and can be prepared from readily available materials and reagents (Scheme ). Pyrrolidine sulfonamide 4a and sulfonamides 4b – 4d , which contain groups that are commonly used to protect the sulfonamide nitrogen (allyl, para- methoxybenzyl (PMB), 2,4-dimethoxybenzyl groups (DMB)), were subjected to n -BuLi and then N -methoxy- N -methyltrifluoroacetamide, which gave β-ketosulfonamides 5a – 5d in good to excellent yields. After some experimentation using the pyrrolidine derivative 5a as a model system, it was found that compound 6a could be obtained in 93% yield using 2.5 equiv of Selectfluor and Li 2 CO 3 in DMF for 3 h. Compound 6a could also be produced in a 78% yield using just 2.5 equiv of Selectfluor in DMF at 100 °C for 1 h (no base added).…”
Section: Resultsmentioning
confidence: 99%
“…(9-Phenyl-9-fluorenyl)-alanal (11). Compound 11 was prepared from 1.08 g (2.9 mmol) of (9-phenyl-9-fluorenyl)alanine methylmethoxyamide according to the general procedure and was obtained as a white solid (808 mg, 89% yield) after flash chromatography (0− 20% EtOAc in hexane).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, only monoalkylated sulfamoyl chloride derivatives were shown to be compatible and the propensity of the S–Cl bond to undergo homolytic cleavage , might lead to side reactions . The reverse strategy, which relies on the Claisen condensation of deprotonated sulfonamide and an ester, remains rare . In 2019, Wang and co-workers reported the transformation of silyl enol ethers into β-ketosulfonamides via a radical process catalyzed by a Ru photocatalyst (Figure a) .…”
mentioning
confidence: 99%